Tourism in peripheral areas : case studies - Hall, Derek, 1948-; Brown, Frances, 1956- (Aspects of tourism, 2000)
"This volume aims to fill a gap by presenting a range of case studies - including northern Sweden, the Orkneys, the tip of Norway and northern Cyprus - on tourism in the peripheral areas of Europe. Taking as a leitmotiv the paradoxes inherent in developing places whose very attraction may lie in their lack of development, the case studies investigate and illustrate both the opportunities and the threats that tourism presents to peripheral areas." "Although they share certain similarities, the cases also demonstrate differing approaches to tourism development and varying outcomes over time. They suggest solutions for dealing with, for example, community participation as well as providing practical insights into visitor perceptions of peripheral areas and into ways of marketing such areas in a sensitive manner. Together they provide a picture of the needs of peripheral areas and of how far and how best tourism can fulfil those needs."--BOOK JACKET.